Distributed control and power quality improvement in hybrid AC/DC microgrids - Jin, Chi (2014)
Global concerns on fossil fuel depletion and environmental pollution have initiated an increasing demand for renewable energy such as solar, wind and fuel cells etc. More distributed generations (DGs) powered by renewable energy sources (RESs) will be entering into the existing electricity network in the near future. Clustering a few DGs, loads and storages together forms entities known as microgrids which merge advantages of individual DG units to arrive at an operating efficiency and system reliability that can never be attained by any single DG. Realization of those advantages accompanies the development of various essential power conditioning interfaces and their associated control for tying multiple DGs to the microgrids, and then tying the microgrids to the traditional power systems. Moreover, the intermittent characteristics of most green sources like photovoltaic (PV) arrays, wind turbines (WT) strongly rely on climatic or environmental condition, which makes RES uncontrollable. To overcome those inherent deficiencies, power electronics is the key enabling technology for the interconnection between RESs and the utility grid, providing more control flexibilities so as to fulfill system reliability and power quality requirements. The proliferation of popular RESs like PV and fuel cells, and energy storages (ESs) like batteries and ultra-capacitors, which are all DC by nature, facilitates widespread application of DC microgrid in many industry systems, commercial buildings and residential complex. The advantages of DC microgrids include better compatibility, higher efficiency and robust stability. To cope with the stochastic nature of RESs, stable operation of a standalone DC microgrid with multiple DC sources, ESs and loads invariably involves the development of flexible and reliable control strategies for power balancing in both power generation and consumption ends. A coordination control scheme among multiple DC sources and ESs interfaces is implemented using a novel hierarchical control technique to maintain DC bus voltage within the limits while harvesting maximum renewable energy and prolonging storage lifetime. Combining the DC microgrid and the dominated AC system forms the scenario — hybrid AC/DC microgrid, which would be, in concept, the presence of both DC and AC microgrids with sources, storages, loads and appropriate interlinking converters (ICs) tied between them. Hybrid AC/DC microgrid has been becoming a popular concept to provide an effective solution for unlimited large-scale integration of various DGs and distributed storages (DSs) because of its higher efficiency and better compatibility. Normal operations of hybrid system include local energy management within each sub-grid and power exchange tuning between two sub-grids, which usually involve multi-layer supervision system and advanced energy management algorithm with vast communication links. However, it is impractical to linkup widely dispersed DGs through communication wirings. This would undoubtedly degrade system redundancy. The challenge is thus to avoid the wiring by developing appropriate decentralized control. With this in mind, a global power sharing (GPS) control is proposed to manage local power sharing (LPS) in individual sub-grid and GPS throughout the entire hybrid system. Due to the load variations at the demand end and the intermittent renewable power at the supply end, the hybrid AC/DC microgrid can hardly be fully autonomous unless the DSs are placed for energy buffering, power balancing and fault riding-through. The storages, such as batteries, ultra-capacitors, flywheels etc., can be configured to behave in different manners according to specific microgrid applications and their respective features. Storages with high energy like batteries are usually placed for long-term system operation, serving as a controlled current source. While the high power storages like ultra-capacitors are usually controlled as a voltage source, maintaining system power balance in transient state. In this sense, different control schemes for DSs would undoubtedly increase the complexity of power management in hybrid AC/DC microgrid in spite of DS locations in AC or DC microgrid. Therefore, fulfilling the requirement of “plug-and-play” is getting difficult since all DSs are not controlled in a coincident way. To avoid the complexity of power management and enforce a coincident control scheme to DSs, a hybrid microgrid scenario with three buses including AC, DC, and DS buses is proposed. LPS in individual sub-grid, GPS throughout entire hybrid system and storage power sharing (SPS) among DS units are well elaborated. To restrain unexpected GPS behaviors and reduce the usage of DSs, a multi-level power exchange control strategy is developed to schedule the activation sequences among LPS, GPS and SPS. The interlinking converter between AC and DC microgrids can be used not only to manage fundamental power flow among two sub-grids but also to serve as an active power filter (APF), drawing harmonic current from AC to DC microgrid so as to improve the power quality in AC sub-grid. The ripple power injected into the DC microgrid results in voltage ripple in DC bus voltage, which is harmful for stable operation of DC system. A DC-link compensator (DLC) is therefore developed to sink the harmonic power, transferring it to auxiliary DLC. In this way, the variation of the DC bus voltage can be limited within an accepted band even with a relative smaller DC-link capacitance. The hierarchical control scheme for standalone DC microgrids, the fully decentralized control for hybrid AC/DC microgrids, the distributed control for hybrid AC/DC/DS microgrids and power quality improvement for hybrid AC/DC microgrid have been verified in theory, simulation and experiment, and will definitely facilitate the application and development of hybrid AC/DC microgrid in low voltage distribution systems.